Relationship of non-nutritive sucking habit towards to malocclusion to the children aged 3-5 years: Hubungan kebiasaan mengempeng terhadap maloklusi pada anak usia 3-5 tahun - Sri Hardiyanti; Eddy Heriyanto Habar (Makassar Dental Journal, 2020)
Background:TheprevalenceofmalocclusioninIndonesiaisstillveryhigh,around80%ofIndonesianpopulation.Oneofthe causes of malocclusion is the bad habit of the oral cavity (non-nutritive sucking). The existence of bad habits that are usually done in children, especially at the age of 3 years can continue to the emergence of abnormalities such as the occurrence of malocclusion. Objective: To find out the relationship non-nutritive sucking towards malocclusion to children aged 3-5 years. Method: This study used analytical observational method with a cross sectional study design with 35 children samples had sedative habit. Data were analyzed using SPSS version 22.0. Result: The relationship with the correlation test between children who had a non-nutritive sucking habit aged 3-5 years with malocclusion severity showed significant results (p < 0.05). The correlation between the two is 0.496 which means that it is a moderate correlation. The results of the influence test with linear regression test between the duration of the assault and the occurrence of malocclusion show significant results having an effect (p < 0.05). Conclusion: There is a relationship between children aged 3–5 years who have a non-nutritive sucking habits to the occurrence of malocclusion. The longer the duration of pressing, the higher the severity of the malocclusion.